Pemanfaatan Novel Kapal Terbang Sembilan Karya M.Yanis Sebagai Sumber Belajar Sejarah Lokal di SMAS Mujahidin Pontianak : Penelitian - Shanti; Ika Rahmatika Chalimi; Haris Firmansyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The use of novel learning resources in learning is a new innovation in history learning so research was carried out to determine the use of the novel Kapal Terbang Sembilan by M. Yanis as a local history learning resource at SMAS Mujahidin Pontianak. This type of research is qualitative research with descriptive form. The data source for this research is Mrs. Annisa Januarsi, S.Pd as a history teacher and student of Class Data analysis techniques include data collection, data reduction, data presentation, and verification/drawing conclusions. Data validity techniques use source triangulation and technical triangulation. The results of the research show that: 1. There are three stages in planning to use the novel Kapal Terbang Sembilan by M. Yanis as a local history learning resource and has been included in the RPP, namely designing learning objectives, adjusting the material, and adjusting the subject schedule. 2. There are two stages in utilizing the novel Kapal Terbang Sembilan by M. Yanis as a learning resource, including the application stage carried out using the lecture method and evaluation in the form of group assignments. 3. The obstacles faced in using the novel Kapal Terbang Sembilan by M. Yanis as a source for learning local history are that the novel is difficult to find both in print and online and there is limited time for students to read the entire contents of the novel.